2011
DOI: 10.1186/1752-0509-5-112
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Mathematical Model of Thrombin-, Histamine-and VEGF-Mediated Signalling in Endothelial Permeability

Abstract: BackgroundEndothelial permeability is involved in injury, inflammation, diabetes and cancer. It is partly regulated by the thrombin-, histamine-, and VEGF-mediated myosin-light-chain (MLC) activation pathways. While these pathways have been investigated, questions such as temporal effects and the dynamics of multi-mediator regulation remain to be fully studied. Mathematical modeling of these pathways facilitates such studies. Based on the published ordinary differential equation models of the pathway component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 101 publications
(127 reference statements)
1
8
0
Order By: Relevance
“…Moreover, we distinguished an acute presence of inter endothelial gaps suggesting an H 2 O 2 -mediated retraction of the cells. We also noticed the same typical morphological pattern with histamine treatment, a potent inducer of endothelial and vascular permeability [32]. Based on these findings, the H 2 O 2 and histamine-mediated changes in the organization of actin seem to be a fast and strong response that contributes to increase stress resistance.…”
Section: Discussionsupporting
confidence: 67%
“…Moreover, we distinguished an acute presence of inter endothelial gaps suggesting an H 2 O 2 -mediated retraction of the cells. We also noticed the same typical morphological pattern with histamine treatment, a potent inducer of endothelial and vascular permeability [32]. Based on these findings, the H 2 O 2 and histamine-mediated changes in the organization of actin seem to be a fast and strong response that contributes to increase stress resistance.…”
Section: Discussionsupporting
confidence: 67%
“…Previous reports showed that glycerophosphatidylcholine concentration typically increases with age; moreover, this increase is more pronounced in aged AD patients and those with enhanced A ␤ plaque formation (29)(30)(31)(32). Breakdown of APP and aggregation of amyloid plaques are the major causes of neuronal deterioration in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Models describing the effects of circulation on endothelial metabolites have also been built ( 123 ). Endothelial NO interactions ( 124 126 ), Ca 2+ signaling ( 127 ) along with protein ( 128 ) and mechanical ( 119 ) signaling have also been addressed with computational modeling. Models have been individualized using patient data and have explored the effects of stenting on blood flow ( 129 132 ).…”
Section: Discussionmentioning
confidence: 99%